Physical measurement of the expansion rate of anisotropic tissue expander in the skin of the horse - Al-Majhali, S. H.; Khairuddin, Nurul Hayah; Mohamad Yusof, Loqman; Radzi, Zamri; Chen, Hui Cheng; Lau, Seng Fong; Rahman, Mohammad Tariqur (Universiti Putra Malaysia Press, 2018)
Tissue expansion technique is one of the most important innovations in skin reconstructive surgery. In this study, anisotropic self-inflating hydrogel tissue expanders were implanted subcutaneously at different anatomical locations; frontal, right shoulder and right forelimb of horses. The resulting skin expansion were observed and recorded daily for the duration of 28 days by manual physical measurements. The rate of height growth and swelling that were recorded are 164.25% at the frontal region of the head, 189.13% at the shoulder region and 122.42% at the forelimb region. The growth of the tissue expander in the three sites could be summarized in three phases; biodegradable in week one, the peak of anisotropic expansion in week two and three, and final degree of swelling in week four.